(untitled) (Al-Academy, 2015)
Summarized the idea of research is marked by "changes in the process of mass communication by using the international network of information" by specifying what data networking and mass communication is the transformation processes in the mass communication network where research aims to:1. Diagnostic data and transformations in the process of mass communication network.2. Provide a contact form commensurate with the characteristic mass of the International Network of electronic information, and research found to provide a communicative model called the (human contact network). In short (HCN) Humanity Communication Net also reached conclusions concerning the search process and communicative transformations and changes that have taken place by (the Internet).1 - Turned the process of public communication in the digital age, the era of the international network of information, bringing a focus on the (the means) instead of (the message) and achieved (the means) creativity in the process of transferring messages connectivity and communication process in general. And so true prophecy (McLuhan), where he said,”the importance of the message lays in a way it transfer."2 - It is a system with two-way.3 - The sender’s effective and can be a receiver and sender at the same time.4 - The future is positive and interactive participant.5 - The means of communication, networking means (vehicle) and multi-media.6 - The process of communication is reciprocal between the source and the receiver.7 - Transfer the messages and data in digital form using (0.1) in the representation.8 - Selective communication of messages by the receiver.9 - Digital communications over the Internet is characterized by (interactive).10 - Electronic communication to achieve the promotion of the message because of communication Interactive Communication Multimedia.11 - The environment clean and safe communication as confusion factors weaken.12 - Public communication is characterized by enrich of the in formations are wide and overlapping.13 - Contact become a (contact computerized), Com-com computer communication